2023
DOI: 10.3390/cancers15041105
|View full text |Cite
|
Sign up to set email alerts
|

Association of Multi-Phasic MR-Based Radiomic and Dosimetric Features with Treatment Response in Unresectable Hepatocellular Carcinoma Patients following Novel Sequential TACE-SBRT-Immunotherapy

Abstract: This study aims to investigate the association of pre-treatment multi-phasic MR-based radiomics and dosimetric features with treatment response to a novel sequential trans-arterial chemoembolization (TACE) plus stereotactic body radiotherapy (SBRT) plus immunotherapy regimen in unresectable Hepatocellular Carcinoma (HCC) sub-population. Twenty-six patients with unresectable HCC were retrospectively analyzed. Radiomic features were extracted from 42 lesions on arterial phase (AP) and portal-venous phase (PVP) M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Similarly, Li et al showed that DVintra_original_glszm_Zone Variance was an independent predictor for free-progression-survival in patients with advanced gastric cancer treated with ICIs [59] . This evidence was also observed with more complex treatment strategy, as in the study by Ho et al where delta radiomics was able to predict response in patients with hepatocellular carcinoma undergoing sequential trans-arterial chemoembolization plus stereotactic body radiotherapy plus immunotherapy [60] .…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, Li et al showed that DVintra_original_glszm_Zone Variance was an independent predictor for free-progression-survival in patients with advanced gastric cancer treated with ICIs [59] . This evidence was also observed with more complex treatment strategy, as in the study by Ho et al where delta radiomics was able to predict response in patients with hepatocellular carcinoma undergoing sequential trans-arterial chemoembolization plus stereotactic body radiotherapy plus immunotherapy [60] .…”
Section: Discussionsupporting
confidence: 54%
“…The R packages used include the following: base package for randomization and normalization; stats package for chi-squared test, Fisher's exact test, Mann-Whitney U test and Spearman's rank correlation coefficients; caret package for pair-wise correlations; glmnet package for logistic regression with the three-fold crossvalidation and LASSO penalty; and ROCR and cvAUC packages for ROC analysis and AUC calculation. A p-value of less than 0.05 represented statistical significance [12,39,[45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the derived radiomics signature was evaluated in terms of accuracy, sensitivity and specificity. Additionally, the average AUC values of the training and testing cohorts were calculated [12,39,[45][46][47][48]. Figure 3 summarizes the feature selection, model development and statistical analysis processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations